Unterritorialized writing: two insufferable discourses of Roberto Bolaño - Ostria Reinoso, Olga (2012)
The works of Roberto Bolaños tend to establish a borderline and marginal relationship with the world in the extent in which they express a moving subjectivity, capable of being read in different levels of the texts and to be interpreted as an “unterritorilized” writing. Such notion allows us to link the author with certain socio-cultural processes –such as migration and new forms of exile– as reinterpreted or reinvented from a contemporary perspective. In sum, the article examines “Los personajes fatales” and “El último lugar del mapa”, from the book Entre paréntesis (2004), which do not fit any of the canonic genres or textual typology since they continually transgress their known boundaries.